Investigation of High School Students’ Conceptual Understanding of Light Waves: Survey in West Java - Syafnah Aisyah Nauli Harahap; Ika Mustika Sari; Dadi Rusdiana (Jurnal Penelitian Pendidikan IPA, 2026)
Conceptual understanding is key to learning. It serves as the groundwork that enables students to apply concepts and build higher-order skills. However, previous studies have shown that students’ conceptual understanding of light waves remains limited, and comprehensive data across multiple regions are still lacking. This study investigates students’ conceptual understanding of light waves in West Java. The sample comprised 189 twelfth-grade students who had completed instruction on light waves, selected using a random sampling technique. Employing a survey design with a quantitative descriptive approach, data were analyzed using Rasch Model techniques. The instrument used was a 29-item multiple-choice Light Phenomena Conceptual Assessment (LPCA) which has been validated and reported as reliable. Based on person logit scores, results indicate that 58.73% of students fall into the low-ability category, 26.98% into the medium category, and 14.29% into the high category. These results indicate that majority of students have not yet attained an adequate level of conceptual understanding and still experience difficulties in understanding light wave concepts, which may limit their problem-solving abilities. These outcomes can inform educators and researchers in designing instructional strategies and learning media to more effectively teach light wave concepts and thereby improve students’ conceptual grasp.